Performance analysis of the photovoltaic water pumping system at an educational institute - Hiranvarodom, Somchai (Frontiers in Engineering Innovation Research, 2005)
Photovoltaic (PV) water pumping system is an appropriate way to supply water in locations where access to electric power is an expensive. Solar energy is a logical solution because maximum water demand occurs during periods of maximum sunshine. Due to the fact that the viability of a solar pump depends on a low initial cost and long working period without maintenanace. Energy efficiency and pimplicity are of paramount importance in the design. The PV water pumping system in this work has been installed at Rajamangala Institute of Technology (main campus), Klong 6, Thanyaburi district, Pathumthani province of Thailand. It is mounted on a small farm to supply the water for pouring water on garden plants. The PV pumping system with 490 (Wp) is able to produce the water averagely of 1,250 liters/day based on the climate data at the design location. The programme computer using visual basic was developed for design PV array sizing and system components.